2003
DOI: 10.1093/pcp/pcg081
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Mutagenesis in a Homologue of a Pi Transporter Gene Confers Arsenate Resistance on Chlamydomonas

Abstract: ;An arsenate-resistant mutant AR3 of Chlamydomonas reinhardtii is a recessive mutant generated by random insertional mutagenesis using the ARG7 gene. AR3 shows about 10-fold resistance against arsenate toxicity compared with the wild type. By using a flanking region of an inserted tag as a probe, we cloned the corresponding wild-type allele (PTB1) of a mutated gene, which could completely complement the arsenate-resistance phenotype of AR3. The size of PTB1 cDNA is about 6.0 kb and it encodes a putative protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…Interestingly, PTB2-PTB3 and PTB5-PTB4 are contiguous, with the transcript from the proximal gene of each pair (PTB2 and PTB5) being most strongly elevated after 24 h of P starvation. No significant increase in the level of PTB1 mRNA was observed during P stress, which is in agreement with the report of Kobayashi et al (24), and the PTB6 transcript could not be detected (data not shown).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, PTB2-PTB3 and PTB5-PTB4 are contiguous, with the transcript from the proximal gene of each pair (PTB2 and PTB5) being most strongly elevated after 24 h of P starvation. No significant increase in the level of PTB1 mRNA was observed during P stress, which is in agreement with the report of Kobayashi et al (24), and the PTB6 transcript could not be detected (data not shown).…”
Section: Resultssupporting
confidence: 93%
“…Congruent with this result, the PTB1 transcript level does not respond significantly to P deprivation conditions. Kobayashi et al (24) have suggested that PTB1 may be involved in intracellular P i transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a relatively rapid, reversible process, adsorption plays an important role in the As detoxification in a wide variety of microalgal species (Jiang et al 2011;Kobayashi et al 2003;Morelli et al 2005;OlguĂ­n and SĂĄnchez-GalvĂĄn 2012;PawlikSkowronska et al 2004). It also holds promise for its potential applications for bioremediation of As in the water environment because it is considered to be a clean technology (Brinza et al 2007) and the As adsorption could reach 60 % of total amount of this element in microalgae (Wang et al 2013c;Zhang et al 2013a).…”
Section: Arsenic Adsorption On Algal Cell Surfacementioning
confidence: 99%
“…P-starved cells also conserve Pi by inhibiting the turnover of chloroplast transcripts by the phosphorylytic chloroplast polynucleotide phosphorylase (Yehudai-Resheff et al 2007). Like Sdeprivation responses, P deficiency-specific responses are often regulated at the level of gene expression, as transcripts encoding extracellular phosphatases and Pi transporters increase markedly in abundance following elimination of P from the growth medium (Kobayashi et al 2003;Chang et al 2005;Moseley et al 2006).…”
Section: Ă mentioning
confidence: 99%